Incised Drawings from Early Phrygian Gordion : Gordion Special Studies IV - Roller, Lynn E. (University Museum monography. Gordion special studies, 2009)
In 1950, the University of Pennsylvania Museum of Archaeology and Anthropology began excavations at the ancient Phrygian capital of Gordion in central Turkey. The Museum's Gordion Project continues today, with researchers from many disciplines and with many specializations contributing to a growing--and sometimes changing--body of information and understanding about this complex and multifaceted site, inhabited by peoples and diverse civilizations for millennia. In this volume of Gordion Special Studies, Lynn E. Roller focuses on a series of stone blocks with incised figural and abstract drawings recovered from early Phrygian structures at Gordion. The great majority of the incised stones come from a single structure within the Early Phrygian citadel at Gordion known as Megaron 2, a stone building with several remarkable features and a likely candidate for the citadel's temple.